BENCH FOR THE DETERMINATION OF THE FORCES MOMENT OF RESISTANCE TO ROTATION OF THE TRUCK RELATIVE TO THE BODY - Ye. P. Blokhin; M. L. Korotenko; V. Ya. Panasenko; R. B. Hranovskyi; I. V. Klymenko; Ye. F. Fedorov (Nauka ta progres transportu, 2009)
In the article 2 variants of stand design for determination of the moment of resistance power to bogie rotation relative to body are described.